Uso de la internet y las tecnologías de información y la comunicación ( TIC’S) en los procesos de enseñanza aprendizaje en la carrera en ciencias de la comunicación social de la Universidad Nacional De Loja - Alvarez Patiño, Karina Elizabeth (2016)
The use of technology today is almost indispensable in all fields of science, being then the tools and services of Information resources of professionals from all areas should be taken into account when performing their tasks, this, this thesis is aimed to diagnose the use and impact of the TIC the Internet in the process of learning among students and teachers of the race in Social Communication Sciences of the National University of Loja. The research part of a theoretical analysis of the role that the Internet TIC's in society, economics and, of course, education. Considering the skills that young students have regarding the use of the internet TIC's against ignorance and disinterest presented by teachers in the use thereof. The thesis inductively address the analysis of preferences, tastes and challenges that teachers and students to use the internet TIC's classroom and socialization with the external environment. To this end, research is based on a questionnaire and conducting a focus group, aimed at students of the School of Science in Social Communication. KEY WORDS: / LEARNING / EDUCATION / INTENET / INFORMATION AND COMMUNICATION TECHNOLOGIES (ICT).